Zustand und Entwicklung ausgewählter Fischbestände: Einschätzung des ICES im Frühjahr 2003 - Gröhsler, Tomas; Zimmermann, Christopher (2003)
During the spring session of the ICES Advisory Committee for Fisheries Management (ACFM) 48 stocks assessed by 7 Working Groups have been analyzed and reviewed, among these all herring stocks in the ICES area, blue whiting and most demersal stocks in the Baltic, Arctic and North-Western area. As in previous years, ICES recommends a reduction in fishing mortality for a number of stocks or even the establishment of recovery and management plans, to safeguard a continuous development of the stocks towards safe biological limits. ICES recommended a 90% reduction of the cod fishery in the Baltic Sea, while most of the herring stocks are in good condition.